A study of X-ray point sources in Heiles Clouds 1 and 2 - Nóra Varga; András Péter Joó; Bendegúz Koncz (Acta Polytechnica)
Star formation takes place in the coldest parts of molecular clouds, beginning in the densest, collapsing regions of filaments. As pre-main sequence stars are luminous X-ray emitters, X-ray point sources can serve as effective tracers of YSOs. In our study, we examined the distribution of X-ray point sources in two nearby molecular clouds: Heiles Cloud 2 (HCL 2), a ring-like molecular cloud complex in the Taurus region, and Heiles Cloud 1 (LDN 1251), a cometary-shaped dark molecular cloud. By incorporating the latest YSO catalogue from Gaia DR3, we analysed how YSO positions compare to the structure of the interstellar medium (ISM) and found that the sources are primarily aligned just outside the densest regions. Additionally, we compared the positions with the magnetic field structure and found no clear correlation at the given resolution.